INTEGRATION OF MADURA LOCAL CULTURE IN CLASS IV SCIENCE CONTENT THEME 2 BANYUAJUH 6 ELEMENTARY SCHOOL - Rusdi Wifahmi; Agung Setyawan; Mohammad Rahbini; Mohammad Usman (Citra Dharma Cindekia, 2022)
Local potential or local culture is a habit or view of residents in an area such as on the island of Madura and can be linked to existing learning in schools, especially science learning. This study aims to determine local potential in Madura which can be integrated into science learning. The method used is descriptive qualitative research. The results of this study indicate that the integration of local potential in learning in schools is very important. This besides being able to increase students' understanding of the material can also provide insight to students regarding local potential in their area so that student awareness will grow and be able to maintain local cultural potential in the future. Local potential integration can be included in science subjects. Some of the local potentials that are included in Banyuajuh 6 are such as Api tak Kunjung Padam which is geothermal and daul music which is a variety of sounds